Impact of Nutrition on Mental Health and Wellbeing of Primary School Children in a rural suburb of Enugu State, Nigeria - Osita Victor Ossai (Didaktika: Jurnal Kependidikan, 2024)
The purpose of this study was to investigate the impact of nutrition on mental health and wellbeing in a rural suburb of Nigeria among primary school children. The study was conducted using an ex post facto design. Using a multi stage and random sampling procedure, 197 primary school children were selected from five migrant farmers schools in a rural suburb in Nigeria. The researcher adapted two instruments: Children’s Mental Health Questionnaire (CMHQ) and Children’s Wellbeing Index (CWI). The Children’s Mental Health Questionnaire (CMHQ) is a 15-item questionnaire which measures the children’s level of depression, anxiety, suicidal thoughts and behaviour. Also, the Children’s Well-being Index (CWI) measures six dimensions of wellbeing such as self-acceptance, life satisfaction, personal growth, positive inter-personal relations, adaptability, and quality of life. The results showed that nutrition significantly impacted on the mental health of primary school children (β = .915; t = 31.1771; p-value = 0.000). Furthermore, the results showed that nutrition significantly impacted the well-being of primary school children (β = .949; t = 42.014; p-value = 0.000). It is recommended that interventions targeted at alleviating the plights of these vulnerable children should be a top priority for the government and non-governmental organizations. It is also further recommended that laudable government programmes such as ‘school feeding programme’ in Nigeria should be revitalized to supplement the diets of school children who are exposed to malnutrition.